CIVIL TORT LAWSUIT AGAINST TRAFFIC ACCIDENT CASES - Cindy Dear Sinaga; Dhea Anastasya Sigalingging; Ardhya Garini; Najwa Azizah Isma; Siti Laura Efida Imran (President University, 2023)
In the contemporary landscape, traffic accidents stand as distressingly common events on our highways, carrying the potential to inflict significant harm on both individuals and property. Despite being frequent occurrences, traffic accidents can result in significant material and non-material losses. While the Criminal Code lacks specific regulations about traffic crimes, Law Number 22 of 2009 concerning Road Traffic and Transport (UULLAJ) addresses these issues. The research focuses on three main areas: 1) Unlawful Acts in Traffic Accidents, 2) Compensation as per Article 1365 of the Civil Code, and 3) the Settlement Process and Determination of Compensation. Through analysis of these key aspects, the study aims to provide insights into the legal framework surrounding traffic accidents and the mechanisms for addressing resultant damages within civil law.Keywords: Accident, Tort, UULLAJ, Lawsuit, Liability;